Inflammatory Pseudotumor in the Epidural Space of the Thoracic Spine: A Case Report and Literature Review of MR Imaging Findings - Seol, Ho Jun; Kim, Sam Soo; Kim, Ji Eun; Lee, Sang Hyung; Won, Jun Yeon (American Journal of Neuroradiology, 2005)
Summary: We present a rare case of pathologically proven inflammatory pseudotumor in the thoracic spine. The lesion showed an isointense signal on T1-weighted images, a heterogeneous iso- and hyperintense signal on T2-weighted images, and strong homogeneous enhancement. There was no evidence of abnormalities in the adjacent bone. Whereas the exact pathogenesis of this lesion is unknown, it has been regarded as an unusual response to insults such as trauma or acute infection, a postinflammatory reparative process, or low-grade malignancy.